2021
DOI: 10.1093/isd/ixab015
|View full text |Cite
|
Sign up to set email alerts
|

The Phylogeographic Shortfall in Hexapods: A Lot of Leg Work Remaining

Abstract: In the 21st century, phylogeography has experienced dramatic growth in the data and methods used by the field. Insect (more generally, hexapod) phylogeography has contributed to major advances and many of the influential papers included hexapods as model systems. In this literature review, we: (i) highlight recent phylogeographic work in hexapod systems, and (ii) identify broader trends and critical future steps in the field. We include a summary of useful methodological approaches and identify the methods use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 199 publications
0
5
0
Order By: Relevance
“…2015; Satler et al. 2021). Recent technological advances provide access to single nucleotide polymorphisms (SNPs) spread throughout the genome (Baird et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2015; Satler et al. 2021). Recent technological advances provide access to single nucleotide polymorphisms (SNPs) spread throughout the genome (Baird et al.…”
Section: Introductionmentioning
confidence: 99%
“…Detecting discordance between the mitochondrial and nuclear genomes requires a complementary approach, with both mitochondrial and nuclear markers sampled from the same individuals. Intraspecific variation, especially if it is recently derived, often necessitates large numbers of independent and variable loci to accurately infer population and demographic histories and to resolve spatial genomic variation (Hey and Nielsen 2004;Carling and Brumfield 2007;Gompert et al 2014;Garrick et al 2015;Satler et al 2021). Recent technological advances provide access to single nucleotide polymorphisms (SNPs) spread throughout the genome (Baird et al 2008;Peterson et al 2012;McCormack et al 2013;Garrick et al 2015) and have been used successfully to resolve spatial genetic variation in many widespread, nonmodel organisms (e.g., Bagley et al 2017;Lumley et al 2020;MacDonald et al 2020;Cairns et al 2021;Polic et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the historical and contemporary factors associated with the distribution of a pest species can provide valuable insights into its biology, ecology, and management in agricultural areas (Corrêa et al 2019, Satler et al 2021). Zucchi et al (2019) reported a high genetic difference between P. guildinii populations from the United States and Brazil and a low genetic difference (and high gene flow) among populations in each country.…”
Section: Introductionmentioning
confidence: 99%
“…The bias toward vertebrate macrogenetics leaves undocumented the bulk of the planet's animal biodiversity: insects. Insects are vital for maintaining critical ecosystem services and functions 32,33 , yet existing insect macrogenetic studies have been restricted to regional scales due to the immense effort required to collect, identify, and sequence such a species-rich taxon [34][35][36][37][38][39] . Studies on the resilience of insect communities to global change 40,41 , including biological invasions 42,43 , habitat conversion 44 , and climate change 45 arrive at conflicting conclusions.…”
Section: Introductionmentioning
confidence: 99%